2014
DOI: 10.2478/folmed-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Memory Effects Of Aronia Melanocarpa Fruit Juice In A Passive Avoidance Test In Rats

Abstract: To study the effect of Aronia melanocarpa fruit juice on memory in male Wistar rats. MATERIALS AND METHODS: The juice was administered orally for 7, 14, 21 and 30 days at doses of 2.5 ml/kg, 5 ml/kg and 10 ml/ kg. Memory was assessed in the one-way passive avoidance task (step through) which consisted of one training session and two retention tests (3 hours and 24 hours after training). The variables measured were the latency time to step into the dark compartment of the apparatus and the learning criterion (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 19 publications
4
30
1
2
Order By: Relevance
“…Percentage of MR was also determined that indicate strong linkage with longterm memory. Valcheva-Kuzmanova et al [63] assessed the effect of Aronia melanocarpa fruit juice on memory in rats by the PA task and also reported similar findings. The RA test was used to examine WR and CR.…”
Section: Discussionsupporting
confidence: 53%
“…Percentage of MR was also determined that indicate strong linkage with longterm memory. Valcheva-Kuzmanova et al [63] assessed the effect of Aronia melanocarpa fruit juice on memory in rats by the PA task and also reported similar findings. The RA test was used to examine WR and CR.…”
Section: Discussionsupporting
confidence: 53%
“…The mean STL of rats treated with the EEPR were ominously higher than those of the other groups. In the study of effect of Aronia melanocarpa fruits juice on memory in rats, Valcheva-Kuzmanova et al, also reported analogous findings [71]. The RA test is used to assess learning and memory based on alteration of The rats brain biochemical parameters were expressed as mean ± SEM values (n = 6/group).…”
Section: Discussionmentioning
confidence: 78%
“…Until now, the protective effects of A. melanocarpa berries and products made from them have been described in regard to heavy metals, such as Cd (Brzóska and others , ,b, ,b; Kowalczyk ; Roszczenko and others ) and Pb (Kowalczyk and others , ), ethanol (Niedworok and others ; Matsumoto and others ; Valcheva‐Kuzmanova and others , ), carbon tetrachloride (CCl 4 ; Valcheva‐Kuzmanova and others ), N‐nitrosocompounds (Atanasova‐Goranova and others ; Kujawska and others ), PAH (benzo‐[a]‐pyrene and 7,12‐dimethylbenz[a]anthracene; Gąsiorowski and others ; Szaefer and others ), sulphide‐2‐chloroethyl‐3‐chloropropyl (Kowalczyk and others ), 2‐amino fluorine (Gąsiorowski and others ), sulfur mustard (Kowalczyk and others ), and some medicines (Niedworok and others ; Valcheva‐Kuzmanova and others , , ; Dietrich‐Muszalska and others ; Figure ). Moreover, A. melanocarpa extract has been reported to protect from the harmfulness of tobacco smoke (Balansky and others ).…”
Section: The Possibility Of Using a Melanocarpa Berries And Their Prmentioning
confidence: 99%
“…Chokeberries should not be confused with chokecherries, which are a different fruit and belong to the Genus Prunus . The results of some studies conducted in animal models indicate that chokeberries seem to be a possible means to counteract the unfavorable health effects of exposure to some xenobiotics (Niedworok and others , ; Kowalczyk and others ,b; Matsumoto and others ; Valcheva‐Kuzmanova and others , ,b; Szaefer and others ; Balansky and others ; Roszczenko and others ; Dietrich‐Muszalska and others ; Navaneethan and Rasool ; Brzóska and others ,b, ,b; Hao and others ). This issue needs special attention because humans in their lifetime are exposed to more and more numerous chemical substances dangerous to their health and some of them contribute to the development of noncommunicable diseases: heart and circulatory diseases, cancers, diabetes, obesity and overweight, digestive system disorders, colds, some skin troubles as well as disorders of the reproductive system and nervous system (Draz and others ; Hsu and others ; Ferraro and others ; Kalariya and others ; Shargorodsky and others ; Bakulski and others ; Choi and others ; Chen and others ; Liu and others ; Moitra and others ; Tellez‐Plaza and others ; Åkesson and others ; Sommar and others ; Wallin and others ; Wu and others ).…”
Section: Introductionmentioning
confidence: 99%